Support and challenges to the melanosomal casing model based on nanoscale distribution of metals within iris melanosomes detected by X-ray fluorescence analysis - Gorniak, Thomas; Haraszti, Tamás; Suhonen, Heikki; Yang, Yang; Hedberg‐Buenz, Adam; Koehn, Demelza; Heine, Ruth; Grunze, Michael; Rosenhahn, Axel; Anderson, Michael G. (Pigment cell & melanoma research, 2014)
Melanin within melanosomes exists as eumelanin or pheomelanin. Distributions of these melanins have been studied extensively within tissues, but less often within individual melanosomes. Here, we apply X-ray fluorescence analysis with synchrotron radiation to survey the nanoscale distribution of metals within purified melanosomes of mice. The study allows a discovery-based characterization of melanosomal metals, and, because Cu is specifically associated with eumelanin, a hypothesis-based test of the ‘casing model’ predicting that melanosomes contain a pheomelanin core surrounded by a eumelanin shell. Analysis of Cu, Ca, and Zn shows variable concentrations and distributions, with Ca/Zn highly correlated, and at least three discrete patterns for the distribution of Cu vs. Ca/Zn in different melanosomes - including one with a Cu-rich shell surrounding a Ca/Zn-rich core. Thus, the results support predictions of the casing model, but also suggest that in at least some tissues and genetic contexts, other arrangements of melanin may co-exist.